Thermal conductivity and thermoelectric performance of SrxBa1−xNb2O6 ceramics at high temperatures. (December 2015) - Li, Yi; Liu, Jian; Hou, Yaqi; Zhang, Yacui; Zhou, Yucheng; Su, Wenbin; Zhu, Yuanhu; Li, Jichao; Wang, Chunlei
Graphical abstract: Abstract: The thermal conductivity of Sr x Ba1− x Nb2 O6 ceramics increases with increasing temperature and exhibits a maximum around the Burns temperature. At the same temperature, the semiconductor–metallic transition occurs in the electron transport. This agreement indicates that the polarized regions have an effect on electrical and thermal transport. Sr x Ba1− x Nb2 O6 ceramics have lower lattice thermal conductivities around the solid solution limitations because of the competing influences caused by increasing Sr content. The figure of merit ZT also exhibits larger values around the solid solution limitations and reaches the maximum of ∼0.2 at 1073 K in Sr0.70 Ba0.30 Nb2 O6 .